Disaster politics: Cyclone politicking and electioneering in the Kingdom of Tonga - Brown Pulu, Teena (Te Kaharoa, 2014)
<span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">Entering the new year of 2014 the Kingdom of Tonga had enough to worry about; a local economy choking to near death and a finance minister sacked and replaced in a political spectacle leaving the public baffled over what went wrong between him and the Prime Minister (Fayle, 2014; Lopeti, 2014c; Fonua, 2014b). People uttered they looked forward to the end of year election tentatively set for Thursday November 27th. The 2010 register of around forty thousand voters had increased at the 2014 intake by four thousand, mostly voters who had turned the age of suffrage at twenty one years old. The chorus call from the masses was simple, <em style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">vote them out<span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">. Then Cyclone Ian struck on Saturday 11 January 2014 aggravating Tonga’s money shortage. <span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">Journalist Pesi Fonua wrote “the impact on the Tongan economy of the cyclone and the salary rise for civil servants at this point of time is a matter of great concern” (Fonua, 2014a). He was right. The state and taxpayers could not afford economic recovery from Tonga’s cruellest cyclone, a symptom of climate change, let alone paying for a 5% rise in the cost of living allowance for public servants. As the national debt distress sore became inflamed the Public Service Association decided it was the right time to fight cabinet for a 22% living allowance rise because 5% was not enough (Lopeti, 2014a). This essay asks a pointed question. Leading up to the general election of November 2014, how was cyclone politicking being manoeuvred to sway the way people would vote?